تأثير التركيب الإثني لسكان العراق على الاستقرار السياسي بعد عام 2003: دراسة في الجغرافية السياسية - الياسري، حسين قاسم محمد فرج (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2022)
يتناول البحث تأثير التركيب الاثني لسكان العراق على الاستقرار السياسي بعد التغيير في نظام الحكم عام ٢٠٠٣ لأهمية هذا التركيب في قوة الدولة، وأظهرت الدراسة أن العراق يضم مجموعة من الأثنيات القومية والدينية، وأن هناك تعايشا سلمي بينها، وقد وضعت تشريعات وقوانين تضمن حقوقها، لكنها لم تلبي طموحاتها كافة، ولهذه الأثنيات امتداد مع دول الجوار وهو ما أسهم في التدخل الخارجي وشكل خطر يهدد الاستقرار السياسي، مما يتوجب العمل على حل مشاكل الأثنيات في العراق من خلال تشكيل لجان دائمة في مجلس النواب والمشاركة السياسية لجميع تلك الأثنيات، وتطبيق اللامركزية الإدارية، والتنمية الشاملة والمستدامة وإجراء تعداد سكاني دقيق، ونشر ثقافة وفنون كل مكونات الشعب العراقي، ومواجهة مخططات الدول الغربية والتيارات السلفية لتكريس روح الفرقة القومية والدينية والمذهبية بتوحيد الخطاب العراقي الخارجي بما يضمن مصلحة العراق وأبناء الشعب العراقي بمكوناته كافه. This paper deals with the impact of the ethnic group of the Iraqi population on political stability after the change in the system of government in 2003 due to the importance of this structure in the power of the state. The study showed that Iraq includes a group of national and religious ethnicities, and that there is a peaceful coexistence between them. It fulfills all its aspirations, and these ethnicities have an extension with neighboring countries that contributed to external interference and posed a threat to political stability, which necessitates work to solve ethnic problems in Iraq through the formation of permanent committees in the House of Representatives and the political participation of all those ethnicities. The application of administrative decentralization, comprehensive and sustainable development Conducting an accurate population census, spreading the culture and arts of all components of the Iraqi people, and confronting the plans of Western countries and Salafi currents to consecrate the spirit of national, religious and sectarian division with the sole Iraqi discourse in a manner that guarantees the interest of Iraq and the Iraqi people with all its components.
Keywords: الجغرافيا السياسية -- التعددية الإثنية -- الإصلاح السياسي -- العراق